Curvature effects on circular feed end-milling, part 1: modelling and simulation. (2015) - Ozoegwu, C.G.; Omenyi, S.N.; Ofochebe, S.M.
Situations needing end milling along a polar feed path normally arise. This is the crux of the matter here. Investigation of such a milling operation led to a non-periodic delay differential equation for its regenerative vibration. To the authors' knowledge this equation is considered to be first of its kind. As a pointer to its validity, the equation is demonstrated to converge to the periodic delay differential equation of linearly fed milling process when the feed path radius approaches infinity. A cutting parameter called angular feed speed which is the ratio of prescribed feed speed to feed path radius is identified and demonstrated to contribute positively to stability of circular milling processes though relative to an equal feed linearly fed end-milling process it plays a progressive destabilising role when on increase. Analysis also led to the conclusion that there is more possibility of tool and machine structural fatigue in circular milling than in a rectilinear milling with equal feed. The subsequent parts of this work are proposed to be focused on the stability analysis and experimental validation of the presented model.